2018
DOI: 10.1002/hbm.24064
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity dynamics in typical development and its relationship to autistic traits and autism spectrum disorder

Abstract: Recent advances in neuroimaging techniques have provided significant insights into developmental trajectories of human brain function. Characterizations of typical neurodevelopment provide a framework for understanding altered neurodevelopment, including differences in brain function related to developmental disorders and psychopathology. Historically, most functional connectivity studies of typical and atypical development operate under the assumption that connectivity remains static over time. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
116
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 58 publications
26
116
1
Order By: Relevance
“…However, a significant positive correlation was found between sustained connectivity and social impairment scores. Similarly, Rashid et al 14 found a link between dynamic functional connectivity and autistic traits assessed using the SRS. These findings also dovetail with electrophysiological results showing delayed auditory evoked responses in autism suggesting temporal prolongation of steady-state responses to stimuli.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, a significant positive correlation was found between sustained connectivity and social impairment scores. Similarly, Rashid et al 14 found a link between dynamic functional connectivity and autistic traits assessed using the SRS. These findings also dovetail with electrophysiological results showing delayed auditory evoked responses in autism suggesting temporal prolongation of steady-state responses to stimuli.…”
Section: Discussionmentioning
confidence: 83%
“…In a study using a sliding-window approach to dynamic connectivity, increased intraindividual variability over time was observed, indicating less rapid switching between networks or states at somewhat longer temporal scales than we measured. 11,14 A recent report investigating lag structure in autism demonstrated differences in the relative lag of individual regions across the brain compared with typically developing control participants, additionally suggesting specific differences in lagged connectivity. 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare state configuration between the ASD and TD groups, we computed two metrics for each state: MDT [Rashid et al, ] and probability of transition (PT). MDT was the average number of windows that were continuous on the time and attributed to the same state [Yao et al, ], and PT was computed as the number of transitions from other states to a specific state over total available transitions (the number of state changes).…”
Section: Methodsmentioning
confidence: 99%
“…focused thoughts in a population of healthy children(Marusak et al, 2017) Rashid et al (2018). demonstrated this state's close associations with high levels of autistic traits and autism spectrum disorder diagnosis.…”
mentioning
confidence: 93%